2009
DOI: 10.1177/0731684409344652
|View full text |Cite
|
Sign up to set email alerts
|

The Tensile Fatigue Behavior of a GFRP Composite with Rubber Particle Modified Epoxy Matrix

Abstract: A thermosetting epoxy polymer was modified by incorporating 9 wt% of a CTBN rubber microparticles. The stress-controlled CA tensile fatigue behavior at stress ratio, R = 0.1 for both the neat and the modified epoxy was investigated. The addition of rubber particles increased the epoxy fatigue life by a factor of about three to four times. The rubber particle cavitation and plastic deformation of the surrounding material was observed to contribute to the enhanced fatigue life of the epoxy polymer. Then, the nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Repeated loading causes these cracks to grow and accumulate until ultimately, a runaway crack leads to rapid, catastrophic failure. The literature has indicated that the addition of rubber [16], metal [13], silica [17] and more recently CNTs [18][19][20][21] and graphene [12,21] positively influence fatigue life and fatigue crack propagation rates when dispersed in epoxy matrices. Grimmer and Dharan [18] suggested that the addition of CNTs to a glass fiber epoxy composite resulted in the adsorption of strain energy through the creation of nanoscale cracks in tension-tension fatigue testing.…”
Section: Introductionmentioning
confidence: 99%
“…Repeated loading causes these cracks to grow and accumulate until ultimately, a runaway crack leads to rapid, catastrophic failure. The literature has indicated that the addition of rubber [16], metal [13], silica [17] and more recently CNTs [18][19][20][21] and graphene [12,21] positively influence fatigue life and fatigue crack propagation rates when dispersed in epoxy matrices. Grimmer and Dharan [18] suggested that the addition of CNTs to a glass fiber epoxy composite resulted in the adsorption of strain energy through the creation of nanoscale cracks in tension-tension fatigue testing.…”
Section: Introductionmentioning
confidence: 99%
“…Manjunatha et al [6] studied the stress-controlled constant amplitude tensile fatigue tests at stress ratio R=0.1 on rubber modified GFRP composites. They showed the fatigue lifetime of GFRP composites laminate increased by a factor of about three times due to the addition of rubber particles in the epoxy matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The residual stiffness degradation of FRP composite subjected to fatigue loading at various R-ratio need to be quantified and the appropriate parameters should be identified from a series of tensile and fatigue tests and for prediction of the residual stiffness for the laminates [9]. The past studies have shown that the fatigue behaviour of composites is highly dependent on the stress ratio R and the frequency of applied cyclic loading [10,11,12,6,13].…”
Section: Introductionmentioning
confidence: 99%
“…This microstructure of the epoxy polymer leads to many valuable properties such as a high modulus and failure strength, low creep, etc., but also directs to an adverse property in that it is moderately brittle and has reasonably poor resistance to crack instigation and propagation. 7 The FRP composite material consists of a polymer that acts as a matrix and a reinforcing material, which is chosen as per preferred applications and properties. In a typical FRP composite, the fiber performs as a typical load-carrying aspirant, while the matrix transmits the load to the fiber and to guard it from any fault.…”
Section: Introductionmentioning
confidence: 99%